Engineering Game Theory of Green Hydrogen towards Energy Transition using Shariah Jurisprudence Developmental Framework based on Ethical Decision-Making from Philosophy of Technology - Llarena, Zharama (International journal of Engineering, Business and Management, 2023)
Green hydrogen is a production of business philosophy inclined to promote renewable energies. Its paradigm shift works on targeting the absence of carbon emissions leading to compliance of the first law of thermodynamics since the financial intelligence of business industries is designed to maintain the abundance of natural resources through economical means. Sustainable development is the result of business growth innovations based on environmental impact assessments concerning marketing of goods and services. However, there are observed restrictions on these contract laws of business transactions, thus, problems can be raised pertaining to monetary intelligence of environmental laws. This paper is designed to address issues on energy transition and elucidate the equation development of statutory interpretation and its gaps to environmental laws and electricity regulations using game theory modelling of shariah jurisprudence method resulting to question development of services, particularly, the hydrogen production and zero target emission of greenhouse gases based on Renewable Energy (Electricity) Bill 2000 (Cth). The legal history of commercial transactions, starting from Hague to Rotterdam Rules are documented to enhance the bill of lading pertaining to transportation of goods in relation to receipt and delivery. Constitutional laws are superior as pre-emption doctrine for compliance and harmony of other statutory laws such as electricity bill and climate change regulations. Energy regulations are observed to comply with climate change policies for tightening the monetary strength of business systems against depletion of environmental resources. Therefore, if green hydrogen is the 2050 plan for electricity transition, its prediction is analogous to the technological services of concession elucidating the equation development of business economics and its environmental laws for public safety in meeting the energy demands resulting zero target emission.